2018
DOI: 10.2147/tcrm.s147696
|View full text |Cite
|
Sign up to set email alerts
|

Raised serum uric acid is associated with higher bone mineral density in a cross-sectional study of a healthy Indian population

Abstract: PurposeOxidative stress has been implicated as a fundamental mechanism in the decline of bone mass. Reactive oxygen species are reported to suppress osteoblast generation and differentiation and enhance osteoclast development and activity. Increasing evidence suggests favorable effect of serum uric acid (UA) on bone metabolism due to its antioxidant properties. Therefore, we investigated the association between serum UA levels and bone mineral density (BMD) in healthy adult Indian subjects.Materials and method… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
13
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 19 publications
(15 citation statements)
references
References 45 publications
2
13
0
Order By: Relevance
“…The study also confirmed no significant association between SUA and total body BMD in young adults, women, non-obese, and smokers. This finding is supported by several epidemiological studies using different study designs and population samples (23,24,(26)(27)(28)(29)(30)(31)(32)(33)(34)(35)(36)(37)(38)(39)(40) as listed in Table 2. These epidemiological studies aimed to elucidate the relation between SUA and bone health.…”
Section: Discussionsupporting
confidence: 64%
See 1 more Smart Citation
“…The study also confirmed no significant association between SUA and total body BMD in young adults, women, non-obese, and smokers. This finding is supported by several epidemiological studies using different study designs and population samples (23,24,(26)(27)(28)(29)(30)(31)(32)(33)(34)(35)(36)(37)(38)(39)(40) as listed in Table 2. These epidemiological studies aimed to elucidate the relation between SUA and bone health.…”
Section: Discussionsupporting
confidence: 64%
“…These epidemiological studies aimed to elucidate the relation between SUA and bone health. Many cross-sectional studies have confirmed the positive association between SUA and BMD in both genders and all age groups after adjustment for potential confounders (28,36,38). In other cross-sectional studies, the positive association was dependant on a significant interaction of SUA level with age and vitamin C level (40), central adiposity, or obesity among postmenopausal women (23,24,26).…”
Section: Discussionmentioning
confidence: 92%
“…The exact mechanism(s) by which all these events occur remains unclear [ 44 , 45 ]. This is to inform that the results for the correlation analysis between BMD and serum UA in a subset of this population have recently been published [ 46 ].…”
Section: Discussionmentioning
confidence: 99%
“…In a study consisting of 310 healthy Indian participants, Kaushal et al (12) categorized indiviuals into two groups based on the uric acid levels and found that height, weight and body mass index (BMI) in the group with serum uric acid 5.4 mg/dL and above were statistically significantly higher compared to the group with serum uric acid below 5.4 mg/dL. They noted that alkaline phosphatase, 25 (OH) D, fasting blood glucose and hemoglobin A1c (HBA1c) levels were similar between the two groups.…”
Section: Discussionmentioning
confidence: 99%